2009
DOI: 10.1194/jlr.m800661-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

OSBP-related protein 2 is a sterol receptor on lipid droplets that regulates the metabolism of neutral lipids

Abstract: Oxysterol binding protein-related protein 2 (ORP2) is a member of the oxysterol binding protein family, previously shown to bind 25-hydroxycholesterol and implicated in cellular cholesterol metabolism. We show here that ORP2 also binds 22(R)-hydroxycholesterol [22(R)OHC], 7-ketocholesterol, and cholesterol, with 22(R)OHC being the highest affinity ligand of ORP2 (K d 1.4 3 10 28 M). We report the localization of ORP2 on cytoplasmic lipid droplets (LDs) and its function in neutral lipid metabolism using the hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(133 citation statements)
references
References 51 publications
7
123
3
Order By: Relevance
“…Knockdown of OSBPL2 expression with RNA interference increased the amounts of triglyceride and cholesterol ester. 22 The presence of OSBPL2 on lipid droplets was consistent with an inhibitory role in triglyceride, phospholipid, and cholesterol ester metabolism. 20,21 This evidence suggests that OSBPL2 plays a major role in the integrated control of cholesterol and triglyceride metabolism.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Knockdown of OSBPL2 expression with RNA interference increased the amounts of triglyceride and cholesterol ester. 22 The presence of OSBPL2 on lipid droplets was consistent with an inhibitory role in triglyceride, phospholipid, and cholesterol ester metabolism. 20,21 This evidence suggests that OSBPL2 plays a major role in the integrated control of cholesterol and triglyceride metabolism.…”
Section: Discussionmentioning
confidence: 73%
“…30,31 Tong et al 32 proved that the unifying role in all ORP homologs was the binding of PI [4]P to ORD, with additional sterol binding for certain homologs, and yeast complementation tests showed that PI [4]P binding to ORD is essential for function. A strictly conserved OSBP-fingerprint motif, "EQVSHHPP, " in the ORD region of OSBPL2 is a specific binding motif for the head of the group of the PI[4]P ligand, suggesting roles as phosphoinositide-binding proteins [20][21][22] (Figure 2e). Although OSBPL2 does not have a pleckstrin homology domain, it had been reported that the ORD region of OSBPL2 plays a role in binding anionic phospholipids analogous to yeast Osh3 and Osh4p.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…140 OSBP and its related proteins have been implicated in regulating numerous cellular processes, which play a central role in HCV life cycle, such as sphingomyelin synthesis, 141 autophagy, 142 and LD biogenesis. 143 In addition, OSBP contains a FFAT motif, conferring the ability to bind to the ER resident VAP (VAMP associated proteins) family of proteins. 140 VAPs represent another group of host cell factors whose involvement in the HCV replication cycle is well documented.…”
Section: Hcv Assembly and Releasementioning
confidence: 99%
“…ORP1S and ORP2 enhance plasma membrane (PM)-to-lipid droplet (LD) sterol transport (Jansen, Ohsaki et al 2011). ORP2 presents on LD and has a functional role in the regulation of neutral lipid metabolism, possibly as a factor that integrates the cellular metabolism of triglycerides (TG) with that of cholesterol (Hynynen, Suchanek et al 2009). ORP3 may play an important role in efficient directed membrane trafficking (Lehto, Mayranpaa et al 2008).…”
Section: Overview Of Functions Of Osbp/orp Family Proteins and Their mentioning
confidence: 99%